Base erosion and profit shifting in South Africa: A critical analysis of the effectiveness of the transfer pricing rules with regard to the elimination of profit shifting - Mpanza, Xolani (My University, 2017)
Tax base erosion and profit shifting (BEPS) is a key tax issue both locally and internationally. Multinational corporations are constantly trying to find means of reducing the amount of taxation that is payable by identifying gaps in tax laws. The aim is to lower the taxation that the group would be liable for. This study will analyse the developments of tax base erosion and profit shifting. There will also be an examination and comparison of South African transfer pricing laws with other countries' tax laws (United State of America, United Kingdom, Australia and Nigeria), specifically with regards to discouraging profit shifting in order not to obtain a tax advantage. Section 31 of the Income Tax Act 58 of 1962, is one of the tools that is currently being utilised by South Africa in addressing the issue of profit shifting. An analysis of Section 31 will be undertaken and it will be necessary to consider whether there are any loopholes or vagueness in the tax laws that may result in taxpayers manipulating the interpretation of the law in order to obtain a tax advantage. Profit shifting is a global problem that has left many countries deliberating on what could be an ideal solution. This study will also propose recommendations that might be used by Commissioner for the South African Revenue Service.
A research report submitted to the Faculty of Commerce, Law and Management, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation
Keywords: Profit shifting; Taxation; Tax base erosion; Transfer pricing; Advanced pricing; Commercial substance